VAKSINASI DALAM PERSPEKTIF ISLAM - Muhammad Mahmud Nasution (IAIN Padangsidimpuan, 2018)
It must be admitted that in the middle of the Islamic world, two different opinions about a law have developed. Some forbid and some others justify it. Of course, each of them comes with all the arguments and reasons that are considered strong and held onto. What is of concern is that the lay community of Muslims, they are drifting in the middle of the vortex of the invitation from each party. Then confused about what to do and what attitude regarding the issue. The status of the halal-haram of vaccination and immunization has become a heated debate and even